The Emerald handbook of the sociology of emotions for a post-pandemic world : imagined emotions and emotional futures - Ward, Paul R.; Foley, Kristen (Emerald handbooks., 2023)
The Emerald Handbook of the Sociology of Emotions for a Post-Pandemic Worldoffers a sociological examination of the lived impacts of the COVID-19 pandemic through culture(s) of emotion, offering a refreshing contribution to a new and exciting sub-discipline.